Advances in the Synthesis of Enterobactin, Artificial Analogues, and Enterobactin-Derived Antimicrobial Drug Conjugates and Imaging Tools for Infection Diagnosis - Klahn, Philipp; Zscherp, Robert; Jimidar, Claire C. (Synthesis, 2022)
Iron is an essential growth factor for bacteria, but although highly abundant in nature, its bioavailability during infection in the human host or the environment is limited. Therefore, bacteria produce and secrete siderophores to ensure their supply of iron. The triscatecholate siderophore enterobactin and its glycosylated derivatives, the salmochelins, play a crucial role for iron acquisition in several bacteria. As these compounds can serve as carrier molecules for the design of antimicrobial siderophore drug conjugates as well as siderophore-derived tool compounds for the detection of infections with bacteria, their synthesis and the design of artificial analogues is of interest. In this review, we give an overview on the synthesis of enterobactin, biomimetic as well as totally artificial analogues, and related drug-conjugates covering up to 12/2021.1 Introduction2 Antibiotic Crisis and Sideromycins as Natural Templates for New Antimicrobial Drugs3 Biosynthesis of Enterobactin, Salmochelins, and Microcins4 Total Synthesis of Enterobactin and Salmochelins5 Chemoenzymatic Semi-synthesis of Salmochelins and Microcin E492m Derivatives6 Synthesis of Biomimetic Enterobactin Derivatives with Natural Tris-lactone Backbone7 Synthesis of Artificial Enterobactin Derivatives without Tris-lactone Backbone8 Conclusions
Keywords: enterobactin; salmochelins; microcins; siderophores; drug conjugates; catecholates; tris-lactone; iron(III) chelator